2011
DOI: 10.1002/hbm.21008
|View full text |Cite
|
Sign up to set email alerts
|

Microglial activation in regions related to cognitive function predicts disease onset in Huntington's disease: A multimodal imaging study

Abstract: Huntington's disease (HD) is an inherited neurodegenerative disorder associated with motor, cognitive and psychiatric deficits. This study, using a multimodal imaging approach, aims to assess in vivo the functional and structural integrity of regions and regional networks linked with motor, cognitive and psychiatric function. Predicting disease onset in at risk individuals is problematic and thus we sought to investigate this by computing the 5-year probability of HD onset (p5 HD) and relating it to imaging pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
141
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(146 citation statements)
references
References 40 publications
(33 reference statements)
5
141
0
Order By: Relevance
“…[9][10][11] Changes in extrastriatal [ 11 C]raclopride binding have also been associated with brain pathologic assesment, such as Parkinson's, Huntington's, and Alzheimer's diseases. [12][13][14] Moreover, a recent study using diffusion-weighted magnetic resonance imaging and PET found that connectivity-based subdivision of human striatum improved the evaluation of regional differences in DA transmission, supporting an association between striatal DA release and cortical connectivity. 35 36,37 In the current study, cortical VAR and ICC values were good to moderate, ranging from 6.1%, 0.79 (temporal cortex) to 13.1%, 0.67 (superior frontal gyrus).…”
Section: Discussionmentioning
confidence: 89%
“…[9][10][11] Changes in extrastriatal [ 11 C]raclopride binding have also been associated with brain pathologic assesment, such as Parkinson's, Huntington's, and Alzheimer's diseases. [12][13][14] Moreover, a recent study using diffusion-weighted magnetic resonance imaging and PET found that connectivity-based subdivision of human striatum improved the evaluation of regional differences in DA transmission, supporting an association between striatal DA release and cortical connectivity. 35 36,37 In the current study, cortical VAR and ICC values were good to moderate, ranging from 6.1%, 0.79 (temporal cortex) to 13.1%, 0.67 (superior frontal gyrus).…”
Section: Discussionmentioning
confidence: 89%
“…Interest in the contribution of inflammation to HD pathology has fostered the study of microglia and their receptors [13,70,71]. Thus, microglial activation may predict an onset of symptoms, but similar to aggregates, the question is unresolved as to whether microglial activation is destructive or protective [72,73]. To date, expression of polyQ-htt directed specifically to, or deleted from, microglia has not been studied.…”
Section: )mentioning
confidence: 99%
“…Cross section analysis of the amygdala has shown a reduced area (Mann et al, 1993) and amygdaloid volume atrophy was detected by MRI studies, which may occur at a very early stage of the disease (Van den Bogaard et al, 2011;Rosas et al, 2003). It should be noted that the reduction of D2/D3 receptor binding and a microglia activation has been observed in the bed nucleus of the stria terminalis, the ventral striatum and the amygdala of premanifest and symptomatic HD gene carriers (Politis et al, 2011). In contrast, Enkephalin, Neuropeptid Y and Neurotensin immunohistochemistry in the central nucleus of the amygdala showed no obvious changes (Zech et al, 1986).…”
Section: Huntington Diseasementioning
confidence: 99%